Determinants of the wholesale prices of energy and ancillary services in the U.S. Midcontinent electricity market. (15th March 2020) - Zarnikau, J.; Tsai, C.H.; Woo, C.K.
Abstract: This paper examines wholesale price behavior of energy and ancillary services (AS) in the day-ahead market (DAM) and real-time market (RTM) of the Midcontinent Independent System Operator (MISO), the second largest regional transmission organization in the U.S. Using hourly data for the period of 12/19/2013 to 12/30/2017, it estimates a system of 16 electricity price regressions that recognizes the interdependence of MISO's electricity products. Its key findings are: (1) MISO's regional DAM energy prices increase with the day-ahead forecasts of natural gas price and MISO's regional loads, PJM's DAM energy price at its MISO interface, and MISO's DAM AS requirements; (2) MISO's regional DAM energy prices decline with DAM schedules for nuclear and wind generation; (3) MISO's regional RTM energy prices increase with, but diverge from, MISO's regional DAM energy prices; (4) MISO's system-average DAM AS prices increase with MISO's system-average DAM energy price and procured amounts of AS; and (5) MISO's system-average RTM AS prices increase with MISO's system-average RTM energy price and system-average DAM AS prices. These findings imply that MISO can reduce its DAM and RTM prices for energy and AS by accelerating wind generation development, expanding demand-side-management, and easing inter-regional transmission congestion. Highlights: Market prices for energy and ancillary services in the MISO electricity market are analyzed. Economic merit order from renewable energy development is quantified. Relationships between day-ahead and real-time prices are examined. Geographical price divergence is analyzed. Opportunities to increase the efficiency of this large market are discussed.